AB0278 Early Termination of the First Biological Disease-Modifying Antirheumatic Drugs Therapy Leads to Radiological Progression in Patients with Rheumatoid Arthritis, Irrespective of Subsequent Therapies. (9th June 2015) - Minegishi, K.; Hama, M.; Yoshimi, R.; Kirino, Y.; Takeno, M.; Ueda, A.; Ishigatsubo, Y.
Abstract : Background: Along with the treat-to-target concept, "hit hard and early" therapeutic strategy has been successful in rheumatoid arthritis (RA), resulting in suppression of radiological progression, particularly in patients receiving biological disease-modifying antirheumatic drugs (bDMARD). However, bDMARD is not always continued due to efficacy and safety issues in daily clinical practice. Objectives: This study investigated impacts of early termination of bDMARS on radiographic progression. Methods: We retrospectively reviewed clinical profiles including X-ay findings of RA patients who initiated a bDMARD as the first biologic agent since 2009 in Yokohama City University hospital. The patients were divided into two groups based on whether the first bDMARD was continued (Group A) or discontinued (Group B) one year later, irrespective of subsequent therapies. At entry, both hands were examined by X-ray and ultrasonography (US). Estimated yearly radiographic progression of the hands was calculated by van der Heijde-modified Sharp score (TSS). Bilateral wrists and all of the metacarpophalangeal and proximal interphalangeal joints were examined by power Doppler and gray scale US semiquantitatively (0-3). Results: Seventy-five patients (84.0% female, mean age 59.7±14.1 years, mean disease duration 7.4±7.9 years) received a first bDMARD (infliximab n=24, etanercept n=10, adalimumab n=9, golimumab n=3, tocilizumab n=22, abatacept n=7). A total of 19 patients (25.3%), including 15 patients who started to receive a second bDMARD within the next year, discontinued initial bDMARD. The reasons of discontinuation were insufficient efficacy (n=9), adverse events (n=9) and other (n=1). At the entry, there was no significant difference in the baseline characteristics including age, gender, disease duration, DAS28, and US scores between Group A and Group B. Group B showed significantly higher DAS28 at one year (p=0.003). Based on TSS of hand X-ray, less radiographic progression was observed in 10 patients (17.9%) of Group A and 8 patients (42.1%) of Group B (p=0.032), respectively. Bone repair was detected in 3 patients of Group A. Estimated yearly radiographic progression was much greater in Group B (1.3±2.1) than Group A (0.4±1.3) (p=0.021). Conclusions: Our data showed that early termination of the first bDMARD within a year was associated with future radiological progression in RA, irrespective of the reasons and subsequent therapies. Thus, appropriate selection of bDMARD in the early phase is critical to suppress bone damage and improve long-term prognosis in RA. Disclosure of Interest: None declared